2013
DOI: 10.1002/asia.201201181
|View full text |Cite
|
Sign up to set email alerts
|

Facile Solvothermal Strategy to Construct Core–Shell Al2O3@CuO Submicrospheres with Improved Catalytic Activity for CO Oxidation

Abstract: In control: A facile solvothermal method was developed to construct core–shell Al2O3@CuO submicrospheres with a controllable shell thickness. Remarkably, the Al2O3@CuO submicrospheres have a much higher activity for CO oxidation than conventional supported CuO/Al2O3 catalysts prepared by a combination of impregnation and calcination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…347 The obtained Al 2 O 3 @CuO core-shell submicrospheres displayed uniform core-shell structures, with shells composed of small CuO NPs (without the formation of CuAl 2 O 4 passivation layer between CuO and Al 2 O 3 ). 347 The obtained Al 2 O 3 @CuO core-shell submicrospheres displayed uniform core-shell structures, with shells composed of small CuO NPs (without the formation of CuAl 2 O 4 passivation layer between CuO and Al 2 O 3 ).…”
Section: Co Oxidation With Core-shell Nanoparticles Chen Et Almentioning
confidence: 92%
See 1 more Smart Citation
“…347 The obtained Al 2 O 3 @CuO core-shell submicrospheres displayed uniform core-shell structures, with shells composed of small CuO NPs (without the formation of CuAl 2 O 4 passivation layer between CuO and Al 2 O 3 ). 347 The obtained Al 2 O 3 @CuO core-shell submicrospheres displayed uniform core-shell structures, with shells composed of small CuO NPs (without the formation of CuAl 2 O 4 passivation layer between CuO and Al 2 O 3 ).…”
Section: Co Oxidation With Core-shell Nanoparticles Chen Et Almentioning
confidence: 92%
“…Chen et al have reported a simple synthetic strategy for making core-shell microspheres consisting of CuO NPs dispersed on the surface of Al 2 O 3 for CO oxidation. 347 The obtained Al 2 O 3 @CuO core-shell submicrospheres displayed uniform core-shell structures, with shells composed of small CuO NPs (without the formation of CuAl 2 O 4 passivation layer between CuO and Al 2 O 3 ). Notably, when these Al 2 O 3 @CuO submicrospheres were used as a catalyst for CO oxidation, a significantly improved activity was observed compared to conventional supported CuO/Al 2 O 3 348 (prepared by impregnation and calcination processes) catalysts in a continuous-flow fixed-bed reactor with feed gas containing 1.0 vol% CO, 1.6 vol% O 2 , and 97.4% He (balance gas) at a total flow rate of 50 mL min À1 , which corresponds to a gas hourly space velocity (GHSV) of 30 000 mL h À1 g cat…”
Section: Oxidation Reactionsmentioning
confidence: 92%
“…In response to this, much research attention has been focused on the development of novel and highly efficient catalysts for CO oxidation and NO x reduction. [4][5][6][7][8][9][10] With a high abundance, cerium oxidation (CeO 2 ) has always been introduced to threeway catalysts for the elimination of engine exhaust pollutants, due to the abundant oxygen vacancy defects, high oxygen storage capacity, and relatively easy shuttles between the III and IV oxidation states, which give rise to enhanced rates of the oxidation reaction. [11][12][13][14] Up until now, intensive efforts have been devoted to CeO 2 supported noble metals such as Ag, Pt, Pd, Ru and Ir, which have remarkably more active and long-term stability as catalysts at a relatively low temperature for CO oxidation reaction and selective catalytic reduction of NO (SCR).…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome this problem, lots of studies have been carried out. [1][2][3][4][5][6][7] Currently, a device with highefficiency energy storage, to be able to store large quantities of electrical energy in a small space and release the energy rapidly, and better cycling stability have been the driving force for the following studies. Transition metal oxide nanostructures are promising electrode materials for supercapacitors because of their high theory specific capacities/capacitances (in general multiple times higher than those of carbon/ graphite-based materials).…”
Section: Introductionmentioning
confidence: 99%